Syntheses related to the preparation of substituted glycosyl derivates of pyrrolo (3,2-f) quinolines : spectroscopic studies of acetylated glycosylamine derivatives - Magnin, Anthony Alan (Department of Chemistry, 2016)
The synthesis of 25 acetylated glycopyranosylamine derivatives (15 of which are newly reported here) from substituted sugar derivatives and amines is described. Eleven different methods were employed in these syntheses. Of the compounds prepared, 15 are substituted glycosylindoline derivatives. The stereospecific synthesis of 1-(2,3,4,6-tetra-0-acetyl-β-D-glucopyranosyl)indoline from 3,4,6-tri-0-acetyl-α-D-glucopyranose l,2-(ethyl orthoacetate) and indoline is reported for the first time. The dehydrogenation of 10 substituted glycopyranosylindoline derivatives to the corresponding glycopyranosylindole derivatives (of which 7 are newly reported) by two methods, is described.